RE-DESIGN CORPORATE IDENTITY BUS PO. SAN DALAM UPAYA MEMBANGUN BRAND IMAGEUNTUK MENJARING PELANGGAN - Wahyu Rinanti; Yusron Wikarya; Ariusmedi . (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
Abstract Bus firms PO. SAN already have a corporate identity corporate identity but are not yet able to reflect the meaning of corporate identity PO.SAN Bus. The purpose of this design is to design the Bus PO coporate identity. SAN in an effort to build a brand image to attract customers. The methodology used in this design is a method of SWOT analysis. Based on the objectives and the methodology used can be produced re-design of corporate identity Bus PO. SAN is expected to build a brand image in an effort to attract customers. The new draft Bus PO logo. SAN is also applied in a variety of media that can support as a means of promotion Po Bus company SAN. Kata kunci: Bus PO.SAN, Corporate identity, Re-Design,Brand Image